(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
In facing the impact of digitalization, it is necessary to control the use of technology. This can be seen from the many cases of gender violence in adolescents. This study aims to investigate the role of Islamic Religious Education (PAI) in dealing with online gender-based violence among adolescents in Cirebon. Through a qualitative phenomenological approach, this research focuses on adolescents’ understanding, perception, and experience of PAI teaching related to the phenomenon of gender violence in the digital realm. In-depth interviews with adolescents, PAI teachers, and related individuals were conducted to explore how the religious values taught in PAI affect adolescents’ attitudes, behaviors, and thoughts towards online gender-based violence. The data analysis carried out includes data reduction, data presentation, and making conclusions. The results of this study are the importance of the role of PAI in shaping the moral and ethical awareness of adolescents against online gender-based violence. Understanding religious values in this context encourages more responsible online behavior and reduces the risk of engaging in gender violence. The implications of this study can be the basis for the development of more effective educational strategies in preventing and tackling online gender-based violence among adolescents.